Results of the Preformed Physical Factors Application in the Rehabilitation Treatment of Corneal Ulcerative Defects - Olga V. Yurova; Tatiana V. Konchugova; Yaroslav A. Soloviev (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2021)
Currently, an infectious corneal ulcer, a defect in the corneal epithelium, remains one of the main causes of monocular blindness,which necessitates the development of new effective methods of treatment. Aim. To develop and evaluate the effectiveness of the technique for the complex application of preformed physical factors of local andsegmental action in patients with corneal ulcers. Material and methods. The study involved 85 patients with corneal ulcers aged 18 to 60 years divided into three groups. Patients ofthe control group (29 people) received the standard drug therapy, the comparison group (29 people) underwent a course of magnetophoresiswith solcoseryl on closed eyelids against the background of standard drug therapy, patients of the main group (27 people)received standard drug therapy, magnetophoresis and low-frequency electrostatic fields on the collar area. All patients were evaluatedfor visual acuity, the size of the ulcer and the area of stromal infiltration. The subjective severity of pain syndrome (VAS scale),psychoemotional state (SAN test) were assessed. Statistical analysis of the data was performed using SPSS Statistics v.25. Results. Immediately after treatment, the use of preformed physical factors made it possible to shorten the period of the ulcer epithelializationand suppression of the inflammatory reaction in the cornea, which significantly improved the clinical and functionalparameters of the eye, as well as considerably reduced the severity of pain syndrome in comparison with standard drug treatment. Conclusion. In the long-term period, the use of preformed physical factors contributed to a significant decrease in the size of thecorneal infiltration area (residual opacities) and an improvement in the quality of life of patients according to the General MentalWellbeing scale, which exceeded the effectiveness of standard drug therapy, while the combined use of a low-frequency electrostaticfield and magnetophoresis allowed to noticeably improve the indicators of visual acuity in comparison with standard drug therapyand isolated use of magnetophoresis.